Шахрайство через електронні комунікації: зауваження до законопроєкту - Зозуля, І. В.; Zozulia, I. V.; Зозуля, О. І.; Zozulia, O. I.; Олександр Зозуля; Зозуля Ігор (Форум права. - 2023. - № 4(77). - С. 63-72, 2023)
Надано оцінку відповідності законопроєкту "Про внесення змін до Кримінального кодексу України щодо встановлення відповідальності за електронно-комунікаційне шахрайство" контексту змісту електронних комунікацій та врахування вимог і викликів сучасного інформаційного суспільства. Встановлено, що з урахуванням широкого поширення сучасних електронних технологій, в останній час особливого значення набула проблема визначення особливостей електронних комунікацій як складової електронно-комунікаційного шахрайства в контексті сучасних тенденцій та розвитку інформаційного суспільства, в тому числі, й щодо використання в правовому полі. Змістом вітчизняного законодавства у контексті електронних комунікацій стало правове осучаснення змісту технологічних новацій, пов'язаних із комунікаційними та інформаційними системами та протидією електронно-комунікаційному шахрайству. Деякими недоліками законопроєкту визначені термінологічна неоднозначність тлумачення визначення "електронно-комунікаційне шахрайство"; можливість існування у кібершахрайстві інших аспектів, не врахованих із заволодінням майном чи отриманням права на майно; можливість становлення неадекватними для нових методів атак чи шахрайства вже сформульованих термінів при швидкому розвитку технологій електронних комунікацій; занадто широкий обсяг визначення із різних аспектів створення, керівництва, участі у шахрайських організаціях та їх спільнотах. Показано, що законопроєкт був викликаний лише ілюзорною можливістю надмірної адаптації сучасного розуміння електронних комунікацій до використовуваних протягом багатьох років норм Кримінального кодексу України стосовно шахрайства, не вдаючись до необґрунтованого змішування понять і категорій. Вирішення проблеми кібершахрайства вимагає більш обережного та обґрунтованого підходу до правового регулювання, де враховувалися би як сучасні виклики, так і вже існуючі стандарти та норми.

In the era of active development of digital technologies and increasing society's reliance on electronic communications, issues of cybersecurity and crimes related to these technologies become extremely relevant. Cybercrime, in particular, is one type of cybercrime that involves the use of information technologies and networks to commit offenses. This has highlighted the need for changes in the legal approach to illegal interventions in the operation of information systems and networks, as well as the necessity to enhance regulatory frameworks in the field of cybersecurity, particularly taking into account modern technological and legal challenges, and improving law enforcement capabilities in responding to cybercrimes. The purpose of the article is to assess the effectiveness and compliance of the bill law "On Amendments to the Criminal Code of Ukraine on Establishing Liability for Electronic Communications Fraud" under registration number 10190 dated October 25, 2023, with the requirements and challenges of the modern information society. The following methods have been employed: legal analysis involving the study, examination, and evaluation of the current legislation regulating fraud via electronic communications, as well as its specific provisions and regulatory acts to clarify their content, logic, and effectiveness; legal critical analysis method to identify inconsistencies, potential negative consequences of introducing new legal norms related to electronic communications in the field of fraud, and consideration of proposals for improving legislation. The results. Established that considering the widespread use of modern electronic technologies, the issue of defining the specifics of electronic communications as a component of electronic communications fraud in the context of current trends and the development of information society has become particularly relevant. In the content of domestic legislation in the context of electronic communications, there has been a legal modernization of the content of technological innovations related to communication and information systems and countering electronic communications fraud. Some drawbacks of the bill law include terminological ambiguity in interpreting the definition of "electronic communications fraud"; the possibility of the existence of other aspects in cyber fraud not considered involving property acquisition or obtaining rights to property; the possibility of becoming inadequate for new methods of attacks or fraud already formulated terms with the rapid development of electronic communications technologies; a too broad scope of definition from various aspects of creating, leading, participating in fraudulent organizations and their communities. Conclusions. The bill was prompted only by the illusory possibility of excessively adapting the modern understanding of electronic communications to the norms of the Criminal Code of Ukraine regarding fraud used for many years, without resorting to the unjustified mixing of concepts and categories. Solving the problem of cyber fraud requires a more cautious and reasoned approach to legal regulation, taking into account both modern challenges and existing standards and norms.

Дана оценка соответствия законопроекта "О внесении изменений в Уголовный кодекс Украины относительно установления ответственности за электронно-коммуникационное мошенничество" контексту содержания электронных коммуникаций с учетом требований и вызовов современного информационного общества. Установлено, что с учетом широкого распространения современных электронных технологий, последнее время особое значение приобрела проблема определения особенностей электронных коммуникаций как составляющей электронно-коммуникационного мошенничества в контексте современных тенденций и развития информационного общества, в том числе и относительно использования в правовом поле.
Fraud via electronic communications: comments to the bill
Keywords: кіберзлочинність; шахрайство; електронні комунікації; законодавство з кібербезпеки; законопроєкт; cybercrime; fraud; electronic communications; cybersecurity legislation; bill; киберпреступность; мошенничество; электронные коммуникации; законодательство по кибербезопасности; законопроект